2019
DOI: 10.1186/s12913-019-4198-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a psychoeducation group intervention conducted by primary healthcare nurses in patients with depression and physical comorbidity: study protocol for a randomized, controlled trial

Abstract: Background Depressive disorders are the third leading cause of consultation in primary care, mainly in patients with chronic physical illnesses. Studies have shown the effectiveness of group psychoeducation in reducing symptoms in depressive individuals. Our primary aim is to evaluate the effectiveness of an intervention based on a psychoeducational program, carried out by primary care nurses, to improve the remission/response rate of depression in patients with chronic physical illness. Secondari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…Estudio transversal realizado con información del momento basal del ensayo clínico «Psicodep», en el que se pretende demostrar la efectividad de una intervención grupal psicoeducativa llevada a cabo por enfermeras de AP 13 .…”
Section: Métodosunclassified
“…Estudio transversal realizado con información del momento basal del ensayo clínico «Psicodep», en el que se pretende demostrar la efectividad de una intervención grupal psicoeducativa llevada a cabo por enfermeras de AP 13 .…”
Section: Métodosunclassified
“…Patients with chronic illnesses often experience psychological distress and related comorbidities, among which anxiety and depression are the most common symptoms (Casañas et al, 2019; Lau‐Walker & Thompson, 2009). Depression is a psychological problem commonly found in CKD cases, with a prevalence rate of 20%.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with available literature. Several studies 15,17,[31][32][33][34][35] reported that progressive muscle relaxation (PMR) is effective in reducing level of anxiety and depression among the elderly.…”
Section: Discussionmentioning
confidence: 99%